The status of the public prosecution in the code of criminal procedure in light of the rule of law standards - Noureddine, Bouselsal (The International tax journal, 2025)
This article examines the status of the Public Prosecution within the Algerian Code of Criminal Procedure in light of the standards of the rule of law. It analyzes the nature of the relationship between the Public Prosecution and the executive authority. The study focuses on the powers granted to the Minister of Justice, particularly in directing criminal policy and supervising members of the Public Prosecution. The findings show that the hierarchical subordination system, the implementation of criminal policy, and the transferability of prosecutors raise several concerns. These issues relate to the extent to which the legal status of the Public Prosecution aligns with the principle of separation of powers and the requirements of judicial independence. The article concludes that institutional reforms are necessary. Such reforms should strengthen the balance between the independence of the Public Prosecution and the need for democratic accountability.